Genetic Dissection and Validation of Chromosomal Regions for Transmission Ratio Distortion in Intersubspecific Crosses of Rice - Zhang, Chaopu; Wang, Dianwen; Wang, Jilin; Sun, Qiang; Tian, Li; Tang, Xinxin; Yuan, Zhiyang; He, Hanzi; Yu, Sibin (Frontiers in Plant Science, 2020)
Transmission ratio distortion (TRD) refers to a widespread phenomenon in which one allele is transmitted by heterozygotes more frequently to the progeny than the opposite allele. TRD is considered as a mark suggesting the presence of reproductive barrier. However, the genetic and molecular mechanisms underlying TRD in rice remain largely unknown. In the present study, a population of backcross inbred lines (BILs) derived from the cross of a japonica cultivar Nipponbare and an indica variety 9311 was utilized to study the genetic base of TRD. A total of eighteen genomic regions were identified for TRD in the BILs. Among them, twelve and six regions showed indica (9311) and japonica (Nipponbare) alleles with preferential transmission, respectively. A series of F2 populations were used to confirm the TRD effects, including six genomic regions that were confirmed by chromosome segment substitution line (CSSL)-derived F2 populations from inter-subspecific allelic combinations. However, none of the regions was confirmed by the CSSL-derived populations from intra-subspecific allelic combination. Furthermore, significant epistatic interaction was found between TRD1.3 and TRD8.1 suggesting that TRD could positively contribute to breaking inter-subspecific reproductive barriers. Our results have laid the foundation for identifying the TRD genes and provide an effective strategy to breakdown TRD for breeding wide-compatible lines, which will be further utilized in the inter-subspecific hybrid breeding programs.